Steel plate and its manufacturing method

A steel plate with a controlled Cu and Ni composition and bainite microstructure, manufactured via hot rolling and accelerated cooling, addresses the challenge of balancing weather resistance and fatigue crack propagation resistance, ensuring durability and safety in high-salt environments.

JP7616164B2Active Publication Date: 2025-01-17JFE STEEL CORP
View PDF 25 Cites 0 Cited by

Patent Information

Application Number
JP2022111548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-19
Filing Date
2022-07-12
Publication Date
2025-01-17
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

Existing steel plates used in outdoor structures, particularly in high-salt environments, face challenges in achieving both excellent weather resistance and fatigue crack propagation resistance, with conventional techniques failing to balance these properties and often requiring frequent maintenance due to paint deterioration.

Method used

A steel plate composition containing specific amounts of Cu, Ni, and bainite microstructure, manufactured through controlled hot rolling and accelerated cooling, to enhance weather resistance and fatigue crack propagation resistance.

Benefits of technology

The steel plate exhibits excellent weather resistance in high-salt environments without painting, reducing maintenance costs and ensuring safety through improved fatigue crack propagation resistance in multiple directions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616164000001
    Figure 0007616164000001
  • Figure 0007616164000002
    Figure 0007616164000002
  • Figure 0007616164000003
    Figure 0007616164000003
Patent Text Reader

Abstract

To provide a steel sheet excellent in weatherability, total elongation and characteristics such as fatigue resistance or crack propagation resistance, and to provide a production method for the steel sheet.SOLUTION: An objective steel sheet is characterized in that the sheet has a component composition consisting of in mass%, 0.010-0.200% of C, 0.05-1.00% of Si, 0.20-2.00% of Mn, 0.001-0.030% of P, 0.0001-0.0350% of S, 0.001-0.100% of Al, 0.10-1.50% of Cu, 0.10-6.00% of Ni and the balance of Fe with inevitable impurities; the microstructure of the sheet includes bainite of 80% or more in area fraction; and the average crystal grain size of the bainite is 50 μm or less in equivalent circle diameter.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet having excellent weather resistance, total elongation, and fatigue crack propagation resistance. The steel plate of the present invention can be suitably used for welded structures such as ships, marine structures, bridges, buildings, tanks, etc., which are used in outdoor atmospheric corrosive environments and for which structural safety is highly required. In particular, the steel plate of the present invention can be suitably used for structures such as bridges used in severe corrosive environments such as on the sea or near the coast where there is a large amount of airborne salt. The present invention also relates to a method for manufacturing the steel plate. [Background technology]

[0002] Steel structures used outdoors, such as bridges, are usually subjected to some kind of anti-corrosion treatment. For example, in environments with low airborne salt content, weathering steel is often used. Weathering steel is a steel material whose surface is covered with a highly protective rust layer in which alloy elements such as Cu, P, Cr, and Ni are concentrated, thereby significantly reducing the corrosion rate when used in an air-exposed environment. It is known that bridges using such weathering steel can withstand decades of service without painting in environments with low airborne salt content. On the other hand, it is known that in high-salinity environments, it is difficult for weathering steel to form a highly protective rust layer, making it difficult to obtain practical weather resistance. For this reason, in environments with high airborne salt content, such as on the sea or near the coast, ordinary steel materials that have been subjected to anti-corrosion treatment such as painting are generally used.

[0003] However, painted steel requires periodic repairs such as repainting due to deterioration of the paint film over time, the occurrence of rust, and swelling of the paint film. The painting work required for repainting is often carried out at high altitudes, which is difficult and increases the labor costs involved. Therefore, when painted steel is used, there is a problem that the repainting work increases the maintenance costs of the structure, which in turn increases the life cycle cost. For these reasons, there is a demand for steel that can be used without painting, even in environments with high levels of airborne salt, such as near the coast.

[0004] In response to such demands, steel materials containing various alloying elements, particularly Ni and Cu, have been developed as steel materials that can be used without painting in high airborne salt environments such as near the coast.

[0005] Here, as an example of a steel material having excellent corrosion resistance, Patent Document 1 discloses a highly coastal weathering steel material containing 0.05 to 1.00% Cu, 0.05 to 7.00% Ni, and 0.005 to 2.000% Pb.

[0006] Patent Document 2 discloses a highly coastal weathering steel material having excellent earthquake resistance, which contains 0.0003 to 0.0050% B and further contains one or more of 0.1 to 1.5% Cu, 0.1 to 6.0% Ni, and 0.005 to 0.500% Mo.

[0007] Patent Document 3 discloses a highly coastal weathering steel material having excellent earthquake resistance, which contains 0.0003 to 0.0050% B and one or more of 0.1 to 2.0% Cu, 0.1 to 6.0% Ni, and 0.005 to 1.000% Mo.

[0008] Patent Document 4 discloses a steel material having excellent coastal weather resistance, which contains 0.0003 to 0.0050% B, 0.3 to 6.0% Ni in the surface layer, and 3.0% or less Ni in the inner layer, and a method for producing the same.

[0009] Patent Document 5 discloses a steel material having excellent coastal weather resistance, containing 0.0003 to 0.0050% B, 1.0 to 6.0% Ni in the surface layer, and 3.0% or less Ni in the inner layer, and a method for producing the same.

[0010] Patent Document 6 discloses a steel material containing 0.1 to 1.5% Cu and 1.52 to 6.00% Ni, which has excellent weather resistance in an environment where snow-melting salt is scattered.

[0011] Patent Document 7 discloses a steel material containing 0.1 to 1.0% Cu and 0.1 to 3.5% Ni and having excellent salt resistance and large heat input welding toughness.

[0012] On the other hand, these steel plates with improved weather resistance are widely used in structures such as ships, marine structures, bridges, buildings, and tanks. The steel plates are required to have excellent mechanical properties such as strength and toughness, as well as excellent weldability, and also excellent fatigue properties. That is, when using the above-mentioned structures, the structures are subjected to repeated loads such as wind, waves, and vibrations due to earthquakes. Therefore, the steel plates are required to have fatigue properties that can ensure the safety of the structures even when such repeated loads are applied. In particular, in order to prevent ultimate destruction such as breakage of members, it is effective to improve the fatigue crack propagation resistance of the steel plates.

[0013] Therefore, various investigations have been conducted to improve the fatigue crack propagation resistance of steel plates.

[0014] For example, Patent Document 8 proposes a steel plate for tankers that has excellent fatigue crack propagation resistance in a wet hydrogen sulfide environment. The steel plate has a mixed structure consisting of ferrite and one or two of bainite and pearlite. The average grain size of ferrite in the steel plate is 20 μm or less.

[0015] Patent Document 9 also proposes a steel plate with excellent fatigue crack propagation resistance. The steel plate has a microstructure consisting of hard parts and soft parts, and is characterized in that the difference in hardness between the hard parts and the soft parts is 150 or more in Vickers hardness.

[0016] Patent Document 10 proposes a dual-phase steel having a microstructure consisting of bainite and 38 to 52% by area of ​​ferrite. The technology proposed in Patent Document 10 improves fatigue crack propagation resistance by controlling the Vickers hardness of the ferrite phase and the number of boundaries between the ferrite phase and the bainite phase per unit length. [Prior art documents] [Patent documents]

[0017] [Patent Document 1] Japanese Patent Application Publication No. 11-315344 [Patent Document 2] JP 2000-355731 A [Patent Document 3] JP 2000-355732 A [Patent Document 4] Patent No. 4232303 [Patent Document 5] Patent No. 4232304 [Patent Document 6] Patent No. 4639482 [Patent Document 7] Patent No. 4792644 [Patent Document 8] Japanese Patent Application Publication No. 06-322477 [Patent Document 9] Japanese Patent Application Publication No. 07-242992 [Patent Document 10] Japanese Patent Application Publication No. 08-225882 Summary of the Invention [Problem to be solved by the invention]

[0018] Although Patent Documents 1 to 7 are all conventional technologies that refer to weather resistance, no consideration was given at all to achieving both weather resistance and fatigue crack propagation resistance, which is an important property for steel plates for structures. In addition, the microstructure of the steel plate is important for improving fatigue crack propagation resistance, and no consideration was given to a manufacturing method for controlling the microstructure.

[0019] In addition, the total elongation value is generally specified in the standards for steel materials used in structures such as ships, marine structures, bridges, buildings, and tanks. Therefore, even steel plates with excellent fatigue crack propagation resistance are required to have a total elongation that satisfies the standard value.

[0020] However, since fatigue crack propagation resistance and total elongation are contradictory properties, the conventional techniques described in Patent Documents 1 to 10 have been unable to achieve both excellent fatigue crack propagation resistance and total elongation.

[0021] In the techniques proposed in Patent Documents 1 to 10, the total elongation is not taken into consideration. In particular, the steel sheets proposed in Patent Documents 8 to 10 all have a microstructure consisting of ferrite as a soft phase and bainite or martensite as a hard phase. The fatigue crack propagation resistance is improved by increasing the hardness difference between the soft phase and the hard phase. However, if the hardness difference between the soft phase and the hard phase is large, the structure becomes inhomogeneous, and as a result, the total elongation of the steel sheet decreases.

[0022] Furthermore, from the viewpoint of ensuring the safety of structures, steel plates are required to have excellent fatigue crack propagation resistance not only in one direction but also in all directions, namely, the plate thickness direction, the rolling direction and the width direction.

[0023] In general structures, steel plates are freely welded from various directions, so fatigue cracks can occur and propagate in various directions. In addition, in welded areas with narrow corners, fatigue cracks are inevitable due to their structural characteristics, and once they occur, they tend to propagate in the plate thickness direction. In order to prevent structures from collapsing due to fatigue cracks, it is important to suppress the propagation of fatigue cracks in the plate width direction and rolling direction even after the fatigue crack penetrates the steel plate in the thickness direction.

[0024] However, the directional dependency of the fatigue crack propagation resistance was not taken into consideration in the conventional techniques described in Patent Documents 1 to 10. Furthermore, the steel materials proposed in Patent Documents 8 to 10 do not have sufficient weather resistance in environments with high levels of airborne salt, such as near the coast.

[0025] The present invention has been made in view of the above circumstances, and has an object to provide a steel plate which can be used without painting even when used in outdoor atmospheric corrosive environments such as bridges, particularly in severe corrosive environments such as at sea or near coasts with high levels of airborne salt, i.e., which has excellent weather resistance, total elongation and fatigue crack propagation resistance, and a manufacturing method thereof. [Means for solving the problem]

[0026] As a result of intensive research aimed at solving the above problems, the inventors have found that adding Cu and Ni in combination is effective for improving weather resistance, that including bainite at a specific area ratio or more as the first phase is effective for improving total elongation, and that adjusting the average grain size of bainite is effective for improving fatigue crack propagation resistance. Furthermore, they have found that a steel sheet having the above microstructure can be manufactured by controlling the manufacturing conditions, in particular, the reduction rate in hot rolling.

[0027] The present invention was completed based on the above findings and through further investigation.

[0028] That is, the gist and configuration of the present invention are as follows. [1] In mass percent, C: 0.010% or more, 0.200% or less, Si: 0.05% or more, 1.00% or less, Mn: 0.20% or more, 2.00% or less, P: 0.001% or more, 0.030% or less, S: 0.0001% or more, 0.0350% or less, Al: 0.001% or more, 0.100% or less, Cu: 0.10% or more, 1.50% or less, Ni: 0.10% or more, 6.00% or less; The balance is Fe and unavoidable impurities. The microstructure of the steel plate contains bainite with an area fraction of 80% or more, The steel plate is characterized in that the average crystal grain size of the bainite is 50 μm or less in terms of circle equivalent diameter. [2] The composition is further expressed as mass percent: Cr:3.00% or less, Mo: 1.00% or less W: 1.00% or less, Co: 1.000% or less, Sn: 0.300% or less, Sb: 0.300% or less, Nb: 0.100% or less, V: 0.150% or less, Ti: 0.100% or less, B: 0.0050% or less, Zr: 0.100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, The steel sheet according to [1], characterized in that it contains one or more selected from the following: REM: 0.0200% or less. [3] Heating a slab having the composition described in [1] or [2] above to a temperature range of 1050°C or more and 1250°C or less, A method for producing a steel sheet, comprising the steps of: after the heating, performing hot rolling with a cumulative rolling reduction of 80% or more in a temperature range below the slab heating temperature and equal to or higher than the Ar3 point. [4] Heating a slab having the composition described in [1] or [2] above to a temperature range of 1050°C or more and 1250°C or less, After the heating, the cumulative rolling reduction in the temperature range of 950°C or higher is 30% or more; A method for producing a steel sheet, comprising hot rolling with a cumulative reduction rate of 30% or more in a temperature range below 950°C and not lower than the Ar3 point. [5] After the hot rolling, accelerated cooling is performed, The method for producing a steel sheet according to [3] or [4], characterized in that in the accelerated cooling, the cooling start temperature is Ar3 point or higher, the cooling stop temperature is 700°C or lower or 400°C or higher, and the average cooling rate on the steel sheet surface from the start of cooling to the end of cooling is 2.0°C / s or higher. Effect of the Invention

[0029] According to the present invention, the steel structure can be used without painting, particularly in bridges and other outdoor atmospheric corrosive environments used at low temperatures in cold regions, particularly in severe corrosive environments such as at sea or near the coast where there is a large amount of airborne salt, or where antifreeze agents are sprayed. Furthermore, the present invention reduces the maintenance costs and thus the life cycle costs of the steel structure, and has excellent fatigue crack propagation resistance and total elongation, and is excellent in fatigue crack propagation resistance in all directions, including the plate thickness direction, the rolling direction, and the width direction, making it possible to ensure the safety of the steel structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The chemical composition, properties, and manufacturing method of the steel sheet of the present invention will be described below in order. Note that the present invention is not limited to the following embodiments.

[0031] First, the chemical composition of the steel sheet of the present invention will be described. In the description of the chemical composition, % indicating the content of each component means % by mass.

[0032] C: 0.010% or more, 0.200% or less C is an element that increases the strength of steel. Therefore, in order to ensure a predetermined strength as structural steel, C must be contained in an amount of 0.010% or more. Therefore, the C content is set to 0.010% or more. On the other hand, if the C content exceeds 0.200%, the weldability and toughness deteriorate. Therefore, the C content is set to 0.200% or less. Furthermore, if the C content is set to less than 0.030%, the amorphous rust ratio in the rust layer increases, which is advantageous for improving weather resistance. Therefore, the C content is preferably less than 0.030%, more preferably 0.025% or less, and even more preferably 0.020% or less.

[0033] Si: 0.05% or more, 1.00% or less In order to ensure deoxidation and strength, it is necessary to include 0.05% or more of Si. Therefore, the Si content is set to 0.05% or more. Preferably, it is set to 0.10% or more. On the other hand, if the Si content exceeds 1.00%, toughness and weldability are significantly deteriorated. Therefore, the Si content is set to 1.00% or less. Preferably, the Si content is set to 0.80% or less.

[0034] Mn: 0.20% or more, 2.00% or less Mn is an element that increases the strength of steel by improving its hardenability. For this reason, Mn must be contained in an amount of 0.20% or more in order to ensure a predetermined strength required for structural steel. Therefore, the Mn content is set to 0.20% or more, and preferably 0.75% or more. On the other hand, if the Mn content exceeds 2.00%, the total elongation, toughness, and weldability deteriorate. Therefore, the Mn content is set to 2.00% or less. The Mn content is preferably set to 1.80% or less.

[0035] P: 0.001% or more, 0.030% or less P is an element that contributes to improving the weather resistance of steel. In order to obtain this effect, P must be contained at 0.001% or more. Therefore, the P content is set to 0.001% or more. On the other hand, if the P content exceeds 0.030%, the weldability and toughness deteriorate. Therefore, the P content is set to 0.030% or less.

[0036] S: 0.0001% or more, 0.0350% or less S is an element that deteriorates weldability and toughness. For this reason, the S content must be 0.0350% or less. Therefore, the S content must be 0.0350% or less. If the S content is reduced to less than 0.0001%, production costs will increase. Therefore, the S content must be 0.0001% or more.

[0037] Al: 0.001% or more, 0.100% or less Al is an element necessary for deoxidation during steelmaking. To obtain such an effect, it is necessary to include 0.001% or more of Al. Therefore, the Al content is set to 0.001% or more. It is preferably set to 0.005% or more, and more preferably set to 0.010% or more. On the other hand, if the Al content exceeds 0.100%, it adversely affects the total elongation and weldability. Therefore, the Al content is set to 0.100% or less. The Al content is preferably set to less than 0.080%, and more preferably set to less than 0.060%.

[0038] Cu: 0.10% or more, 1.50% or less Cu has the effect of forming a dense rust layer by refining the rust grains in the rust layer, and suppressing the permeation of oxygen and chloride ions, which are corrosion-promoting factors, into the base steel. Such an effect can be obtained when the Cu content is 0.10% or more. Therefore, the Cu content is set to 0.10% or more. The Cu content is preferably 0.15% or more, and more preferably 0.20% or more. On the other hand, if the Cu content exceeds 1.50%, the weldability is impaired and defects are more likely to occur during the production of the steel sheet. Therefore, the Cu content is set to 1.50% or less. The Cu content is preferably 1.00% or less, and more preferably 0.80% or less.

[0039] Ni: 0.10% or more, 6.00% or less Ni improves low-temperature toughness and improves hot brittleness when Cu is added. In addition, it forms a dense rust layer by refining the rust grains in the rust layer, and has the effect of suppressing the penetration of oxygen and chloride ions, which are corrosion-promoting factors, into the base steel. Such an effect is obtained when the Ni content is 0.10% or more. Therefore, the Ni content is set to 0.10% or more. The Ni content is preferably 0.50% or more, more preferably 1.00% or more, even more preferably more than 2.00%, even more preferably 2.20% or more, and most preferably 2.40% or more. On the other hand, if the Ni content exceeds 6.00%, the weldability is impaired and the alloy cost increases excessively. Therefore, the Ni content is set to 6.00% or less. The Ni content is preferably less than 5.00%, more preferably 4.00% or less.

[0040] A steel sheet according to one embodiment of the present invention may have a composition containing the above elements with the balance being Fe and unavoidable impurities.

[0041] In addition, the composition of the steel plate in another embodiment of the present invention may further contain at least one of the following elements. By containing these optional elements, the properties such as strength, toughness, weldability, and weather resistance of the steel plate can be further improved.

[0042] Cr:3.00% or less Cr is an element that has the effect of further improving strength. In addition, Cr has the effect of forming a dense rust layer to further improve weather resistance. When Cr is contained, the Cr content is preferably 0.01% or more in order to obtain the above effect. On the other hand, if the Cr content exceeds 3.00%, the weldability and toughness are impaired, and weather resistance is also adversely affected. Therefore, when Cr is contained, the Cr content is set to 3.00% or less. The Cr content is preferably 2.00% or less, more preferably 1.00% or less.

[0043] Mo: 1.00% or less Mo dissolves during the anodic reaction of steel and forms MoO4 in the rust layer. 2- The distribution of Mo prevents chloride ions, which are corrosion accelerating factors, from penetrating the rust layer and reaching the base steel. In addition, compounds containing Mo are precipitated on the steel surface, suppressing the anodic reaction of the steel. When Mo is contained, it is preferable to contain Mo at 0.03% or more in order to obtain such an effect. On the other hand, if the Mo content exceeds 1.00%, the weldability and toughness are impaired, leading to an increase in alloy costs. Therefore, when Mo is contained, the Mo content is 1.00% or less. The Mo content is preferably 0.80% or less, more preferably 0.50% or less.

[0044] W: 1.00% or less W is an element that improves the weather resistance of steel. W dissolves during the anodic reaction and forms WO4 in the rust layer. 2-By distributing W as tungsten, chloride ions, which are corrosion-promoting factors, are electrostatically prevented from penetrating the rust layer and reaching the base steel. Furthermore, compounds containing W are precipitated on the steel surface, suppressing the anodic reaction of the steel. In addition, by forming fine rust and densifying the rust layer, chloride ions, which are corrosion factors, are prevented from penetrating the rust layer and reaching the base steel. When W is contained, in order to fully obtain these effects, it is preferable that W is contained in an amount of 0.01% or more. More preferably, it is 0.03% or more. On the other hand, if the W content exceeds 1.00%, it will lead to a significant increase in alloy cost. Therefore, when W is contained, the W content is 1.00% or less. The W content is preferably 0.70% or less, more preferably 0.50% or less.

[0045] Co: 1.000% or less Co is distributed throughout the rust layer and has the effect of improving weather resistance by forming a dense rust layer. When Co is contained, in order to obtain this effect, the Co content is preferably 0.010% or more, more preferably 0.350% or more. On the other hand, even if the Co content is higher than 1.000%, the effect is saturated and the alloy cost increases. Therefore, when Co is contained, the Co content is 1.000% or less. The Co content is preferably 0.500% or less.

[0046] Sn: 0.300% or less Sn is an element that improves the weather resistance of steel. Sn is present in the rust layer near the surface of the base steel, and by refining the rust particles, it prevents chloride ions, which are corrosion-promoting factors, from penetrating the rust layer and reaching the base steel. Sn also suppresses the anodic reaction on the steel surface. When Sn is contained, in order to fully obtain such effects, it is preferable that the Sn content is 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if the Sn content exceeds 0.300%, the ductility and toughness of the steel are deteriorated. Therefore, when Sn is contained, the Sn content is 0.300% or less. The Sn content is preferably 0.100% or less, and more preferably 0.050% or less.

[0047] Sb: 0.300% or less Sb is present in the rust layer near the surface of the base steel, and by refining the rust particles, it prevents chloride ions, which are corrosion-promoting factors, from penetrating the rust layer and reaching the base steel. Sb also suppresses the anodic reaction on the steel surface. When Sb is contained, in order to fully obtain such effects, it is preferable that the Sb content is 0.005% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if the Sb content exceeds 0.300%, it will cause deterioration of the ductility and toughness of the steel. Therefore, when Sb is contained, the Sb content is 0.300% or less. The Sb content is preferably 0.150% or less, more preferably 0.100% or less.

[0048] Nb: 0.100% or less Nb is an element that has the effect of suppressing the recrystallization of austenite during hot rolling and refining the crystal grains finally obtained. In addition, Nb precipitates during air cooling, further improving strength. When Nb is contained, the Nb content is preferably 0.005% or more in order to obtain the above effect. On the other hand, when the Nb content exceeds 0.100%, the hardenability becomes excessive, martensite is generated, and the desired structure cannot be obtained, and the toughness decreases. Therefore, when Nb is contained, the Nb content is 0.100% or less. The Nb content is preferably 0.040% or less.

[0049] V:0.150% or less V precipitates during air cooling, further improving strength. In addition, VO4 3- The presence of V as a cation prevents chloride ions, which are corrosion-accelerating factors, from penetrating the rust layer and reaching the base steel. When V is contained, it is preferable to contain 0.005% or more of V in order to fully obtain this effect. On the other hand, when the V content exceeds 0.150%, the effect saturates. Therefore, when V is contained, the V content is set to 0.150% or less.

[0050] Ti:0.100% or less Ti is an element that increases strength. When Ti is contained, it is preferable to contain 0.005% or more of Ti in order to fully obtain this effect. On the other hand, if the Ti content exceeds 0.100%, it leads to a deterioration in toughness. Therefore, when Ti is contained, the Ti content is set to 0.100% or less.

[0051] B: 0.0050% or less B is an element that has the effect of increasing hardenability, and as a result, further improving strength. When B is contained, the B content is preferably 0.0001% or more in order to obtain the above effect. On the other hand, when the B content exceeds 0.0050%, the hardenability becomes excessive, martensite is generated, and the desired structure cannot be obtained, and the weldability is deteriorated. Therefore, when B is contained, the B content is 0.0050% or less. The B content is preferably 0.0030% or less.

[0052] Zr: 0.100% or less Zr is an element that increases strength. When Zr is contained, it is preferable to contain 0.005% or more of Zr in order to fully obtain this effect. On the other hand, when the Zr content exceeds 0.100%, the strength improving effect is saturated. Therefore, when Zr is contained, the Zr content is set to 0.100% or less.

[0053] Ca:0.0100% or less Ca is an element that fixes S in steel and improves the toughness of the weld heat affected zone. When Ca is contained, it is preferable to contain 0.0001% or more of Ca in order to fully obtain this effect. On the other hand, if the Ca content exceeds 0.0100%, the amount of inclusions in the steel increases, which leads to a deterioration in toughness. Therefore, when Ca is contained, the Ca content is set to 0.0100% or less.

[0054] Mg: 0.0100% or less Mg is an element that fixes S in steel and improves the toughness of the welded heat affected zone. When Mg is contained, it is preferable to contain 0.0001% or more of Mg in order to fully obtain this effect. On the other hand, if the Mg content exceeds 0.0100%, the amount of inclusions in the steel increases, which leads to a deterioration in toughness. Therefore, when Mg is contained, the Mg content is set to 0.0100% or less.

[0055] REM: 0.0200% or less REM (rare earth metals) are elements that fix S in steel and improve the toughness of the weld heat affected zone. When REM is contained, it is preferable to contain 0.0001% or more of REM in order to fully obtain this effect. On the other hand, if the REM content exceeds 0.0200%, the amount of inclusions in the steel increases, which actually leads to a deterioration of toughness. Therefore, when REM is contained, the REM content is set to 0.0200% or less.

[0056] Next, the microstructure of the steel sheet of the present invention will be described.

[0057] The steel sheet according to one embodiment of the present invention has a microstructure containing 80% or more bainite by area fraction and an average crystal grain size of bainite of 50 μm or less in equivalent circle diameter. The microstructure in the present invention refers to the microstructure at 1 / 4 position of the sheet thickness t of the steel sheet (1 / 4t position). The area fraction and average crystal grain size of each structure can be measured by subjecting a cross section of the steel sheet parallel to the rolling direction at 1 / 4 depth from the surface to nital etching and observing the cross section. More specifically, the area fraction and average crystal grain size can be determined by the method described in the examples.

[0058] Area fraction of bainite: 80% or more In the present invention, bainite is the first phase in the microstructure. Bainite has a higher effect of suppressing crack propagation than other structures. Therefore, by making the area fraction of bainite 80% or more, it is possible to suppress the propagation of fatigue cracks. If the area fraction of bainite is less than 80%, it is not possible to obtain the desired fatigue crack propagation resistance. Therefore, the area fraction of bainite is set to 80% or more. It is preferable that the area fraction of bainite is set to 85% or more.

[0059] Average grain size of bainite: 50μm or less By refining bainite, it is possible to obtain the desired toughness and total elongation characteristics. If the average grain size of bainite exceeds 50 μm in average equivalent circle diameter, the desired toughness cannot be obtained. For this reason, the average grain size of bainite is set to 50 μm or less in average equivalent circle diameter. The average grain size of bainite is preferably set to 30 μm or less. The average grain size of bainite is more preferably set to 20 μm or less. On the other hand, although there is no particular lower limit for the average grain size of bainite, excessive refinement makes production difficult, so in actual production, it is preferable that the average grain size of bainite is set to 5 μm or more.

[0060] In the present invention, bainite includes upper bainite, acicular ferrite, and granular bainite.

[0061] The steel sheet according to an embodiment of the present invention has a microstructure mainly composed of bainite (B). However, the microstructure may further include other structures as desired. Hereinafter, structures other than bainite are referred to as "other structures". The other structures may include, for example, martensite (Ms), ferrite (F) and pearlite (P). Here, the martensite mentioned above includes island martensite, lath martensite and lenticular martensite, the ferrite mentioned above includes polygonal ferrite, and the pearlite mentioned above includes pearlite and pseudo-pearlite.

[0062] When the microstructure of the steel sheet includes other structures, it is more preferable that the area fraction (total area fraction) of the other structures described above is limited as follows. If martensite is present in excess, a high hardness region is formed locally, and although the strength increases, the total elongation decreases and the toughness may decrease. In particular, if martensite with a hardness of 300HV or more is dispersed at 10% or more, the martensite with a hardness of 300HV or more becomes the starting point (mechanism) of fracture, so the total elongation and toughness decrease significantly. Therefore, it is preferable that the martensite with a hardness of 300HV or more is less than 10%. Furthermore, if ferrite is present in excess, in addition to the decrease in strength and the deterioration of the fatigue crack propagation rate, soft regions are formed locally, and the total elongation may decrease due to the increase in hardness difference. Therefore, it is preferable that the ferrite is 10% or less. Furthermore, since the total elongation decreases with the increase in hardness difference, it is preferable that the hardness difference between different phases is 100HV or less. Therefore, it is preferable to keep the total area fraction of structures other than bainite at 20% or less, and among the other structures mentioned above, it is preferable to keep martensite of 300 HV or more to less than 10%, and it is also preferable to keep ferrite at 10% or less, and it is preferable to keep the hardness difference between different phases in the base material to 100 or less.

[0063] In other words, the steel sheet in one embodiment of the present invention is The microstructure may be 80-100% bainite and 0-20% other structures than bainite. As for the structures other than bainite, it is preferable that martensite of 300 HV or more is less than 10%, and ferrite is preferably 10% or less.

[0064] In the present invention, there is no particular upper limit on the plate thickness, but the present invention is particularly suitable for use with relatively thin steel plates, and therefore the plate thickness of the steel plate in the present invention is preferably 50 mm or less.

[0065] In the present invention, the tensile strength, yield stress, total elongation, and fatigue crack propagation resistance are not particularly limited, but are preferably applied.

[0066] Tensile strength The steel sheet of the present invention has the above-mentioned composition and microstructure, and as a result, has excellent tensile strength (TS). The value of TS is not particularly limited, but is preferably 500 MPa or more, more preferably 530 MPa or more, and even more preferably 550 MPa or more. On the other hand, the upper limit of TS is not limited either, but is preferably 720 MPa or less, more preferably 700 MPa or less, even more preferably 640 MPa or less, and most preferably 620 MPa or less.

[0067] Yield Stress The yield stress (YS) of the steel sheet of the present invention is not particularly limited, but is preferably 420 MPa or more, more preferably 430 MPa or more, and even more preferably 440 MPa or more. Also, the YS is preferably 560 MPa or less, more preferably 530 MPa or less, and even more preferably 520 MPa or less.

[0068] Toughness The steel plate of the present invention has excellent toughness as a result of having the above-mentioned composition and microstructure. The toughness of the steel plate of the present invention is not particularly limited, but the Charpy absorbed energy vE0 at 0°C, which is one of the indicators of toughness, is preferably 100J or more, more preferably 130J or more, even more preferably 150J or more, and most preferably 200J or more. On the other hand, the upper limit of vE0 is not limited, but is preferably 400J or less, more preferably 300J or less, and even more preferably 270J or less. Note that vE0 can be measured by the method described in the examples.

[0069] Total Elongation The steel sheet of the present invention has an excellent total elongation (EL) as a result of having the above-mentioned composition and microstructure. The value of EL is not particularly limited, but is preferably 15% or more, more preferably 16% or more, even more preferably 17% or more, and most preferably 20% or more. The upper limit of EL is also not particularly limited, but is preferably, for example, 30% or less. EL can be measured by the method described in the examples.

[0070] Fatigue crack propagation resistance The steel sheet of the present invention has the above-mentioned composition and microstructure, and as a result, has excellent fatigue crack propagation resistance in all directions, namely, the thickness direction, the rolling direction, and the width direction. The fatigue crack propagation rate (da / dN) can be used as an index of fatigue crack propagation resistance. The value of the fatigue crack propagation rate is not particularly limited.

[0071] It is preferable that the fatigue crack propagation rate in the plate thickness direction (Z direction) satisfies the following conditions (a) and (b). (a) Stress intensity factor range ΔK: 15 MPa / m 1 / 2 The fatigue crack propagation rate under the condition is 8.75×10 -9 (m / cycle) or less, (b) Stress intensity factor range ΔK: 25 MPa / m 1 / 2 The fatigue crack propagation rate under the condition is 4.25×10 -8 (m / cycle) or less In addition, it is preferable that either the fatigue crack propagation rate in the rolling direction (L direction) or the fatigue crack propagation rate in the width direction (C direction) satisfy the following conditions (c) and (d), and it is more preferable that both satisfy conditions (c) and (d). (c) Stress intensity factor range ΔK: 15 MPa / m 1 / 2 The fatigue crack propagation rate under the condition is 1.75×10 -8 (m / cycle) or less, (d) Stress concentration factor range ΔK: 25 MPa / m 1 / 2 The fatigue crack propagation rate under the condition is 8.50×10 -8 (m / cycle) or less Next, a method for manufacturing a steel sheet according to the present invention will be described. A steel sheet according to an embodiment of the present invention can be manufactured by subjecting a steel material having the above-mentioned composition to the following steps (1) and (2), and, if necessary, step (3). (1)Heating (2) Hot rolling (3) Accelerated cooling The conditions for each step are explained below. Unless otherwise specified, the temperature refers to the surface temperature of the workpiece (steel material or hot-rolled steel sheet). The cooling rate refers to the cooling rate at the average temperature in the thickness direction of the steel sheet.

[0072] Any steel material can be used as long as it has the above-mentioned composition. The composition of the final steel sheet is the same as that of the steel material used. For example, a steel slab can be used as the steel material.

[0073] (1)Heating process Heating temperature: 1050℃ or higher, 1250℃ or lower First, the steel material is heated to a temperature range of 1050°C or more and 1250°C or less. If the heating temperature is less than 1050°C, the temperature required for the subsequent hot rolling cannot be ensured. On the other hand, if the heating temperature exceeds 1250°C, the crystal grains of the steel become coarse and the toughness deteriorates. If the steel is held in the heating process, the holding time is preferably 1 hour or more.

[0074] (2) Hot rolling Next, the heated steel material is hot-rolled to produce a hot-rolled steel sheet. In order to produce a steel sheet that satisfies the conditions of the present invention, the cumulative reduction ratio in the hot rolling needs to satisfy any one of the following conditions.

[0075] (2-1) Cumulative reduction rate in the temperature range below slab heating temperature and above Ar3 point: 80% or more By setting the cumulative reduction rate at the temperature range of the Ar3 point or higher to 80% or more, the austenite grains are refined, and the bainite formed by transformation during accelerated cooling is refined. If the reduction rate at the Ar3 point or higher is less than 80%, the refinement of the bainite becomes insufficient, and the toughness and total elongation deteriorate. On the other hand, the upper limit of the cumulative reduction rate at the temperature range of the Ar3 point or higher is not particularly limited, but for example, it is preferably 90% or less, and more preferably 85% or less.

[0076] (2-2) Even if the cumulative rolling reduction in the temperature range below the slab heating temperature and equal to or higher than the Ar3 point is less than 80%, the desired structure and properties can be obtained by satisfying both of the following conditions.

[0077] Cumulative reduction rate at temperatures above 950℃: 30% or more By setting the cumulative reduction rate at 30% or more in the temperature range of 950°C or more, the austenite grains are refined. As a result, the bainite formed by transformation during accelerated cooling is refined. If the cumulative reduction rate is less than 30%, the refinement of bainite is insufficient, and the toughness and total elongation are deteriorated. On the other hand, the upper limit of the cumulative reduction rate at a temperature range of 950°C or more is not particularly limited, but for example, 70% or less is preferable.

[0078] Cumulative rolling reduction rate in the temperature range below 950℃ and above Ar3 point: 30% or more By setting the cumulative reduction rate at 30% or more in the temperature range below 950°C and above the Ar3 point, the austenite grains are refined and the bainite formed by transformation during accelerated cooling is refined. If the reduction rate at or above the Ar3 point is less than 30%, the refinement of bainite becomes insufficient, and the toughness and total elongation deteriorate. On the other hand, the upper limit of the cumulative reduction rate at or above the Ar3 point and below 950°C is not particularly limited, but for example, 70% or less is preferable.

[0079] Here, the Ar3 point can be calculated by the following formula. Ar3(℃)=910-310C-80Mn-20Cu-15Cr-55Ni-80MoIn the above formula, the element symbol represents the content (mass%) of the corresponding element in the steel material, and if the element is not contained in the steel material, it is set to zero.

[0080] (3) Accelerated cooling Next, it is preferable to accelerate cooling the hot-rolled steel sheet obtained in the hot rolling step as required. Various properties are improved by setting the accelerated cooling conditions as follows.

[0081] Cooling start temperature: Ar3 points or higher If the cooling start temperature in the accelerated cooling is less than the Ar3 point, ferrite and coarse pearlite will precipitate excessively, so in order to further improve the strength and fatigue crack propagation resistance, it is preferable to set the cooling start temperature to the Ar3 point or higher. On the other hand, although there is no particular upper limit to the cooling start temperature, it is preferable to set it to 870°C or lower from the viewpoint of ensuring the cumulative rolling reduction in the temperature range of the Ar3 point or higher. In addition, the cooling start temperature being equal to or higher than the Ar3 point necessarily means that the rolling end temperature is equal to or higher than the Ar3 point. If the rolling end temperature is lower than the Ar3 point, the rolling will be in the two-phase region, and the total elongation will be deteriorated, but if the rolling end temperature is equal to or higher than the Ar3 point, the rolling will be performed in the austenite single-phase region, and deterioration of the total elongation can be prevented.

[0082] Cooling stop temperature: 700℃ or less, 400℃ or more, In order to transform untransformed austenite into bainite, the cooling stop temperature in the accelerated cooling is preferably 700°C or less, more preferably 650°C or less. If the cooling stop temperature exceeds 700°C, ferrite is generated, so the increase in fatigue crack propagation resistance is small. On the other hand, if the cooling stop temperature is less than 400°C, the amount of martensite generated increases, resulting in a decrease in toughness and total elongation, so the increase in fatigue crack propagation resistance is small. Therefore, the cooling stop temperature is preferably 400°C or more, more preferably 410°C or more.

[0083] Average cooling rate: 2.0℃ / s or more The average cooling rate in the accelerated cooling is preferably 2.0°C / s or more. If the average cooling rate is less than 2.0°C / s, ferrite is generated, and the increase in fatigue crack propagation resistance is small. Furthermore, the toughness is reduced, and the increase in the desired total elongation is small. The average cooling rate refers to the average cooling rate on the steel plate surface from the start of the accelerated cooling to the end of the accelerated cooling.

[0084] The method for carrying out the accelerated cooling is not particularly limited, and any method can be used, but it is preferable to use water cooling.

[0085] The treatment after the accelerated cooling is not particularly limited. For example, the steel sheet after the accelerated cooling can be allowed to cool in the atmosphere. In the above-mentioned cooling, the steel sheet can be cooled to room temperature, for example. After the accelerated cooling, the steel sheet can be optionally straightened by a leveler to correct the warpage.

[0086] After hot rolling, the temperature of the steel sheet immediately drops, and therefore the steel sheet of the present invention is preferably produced by an online process using equipment in which a rolling device and an accelerated cooling device are provided on a transfer line. EXAMPLES

[0087] The effects of the present invention will be described below using examples, but the present invention is not limited to the following examples.

[0088] The steel plates were manufactured according to the following procedure.

[0089] First, a steel slab (steel material) having the composition shown in Table 1 was produced by a converter-continuous casting method. Next, the steel slab was heated to the heating temperature shown in Table 2, and then hot rolled at the cumulative rolling reduction shown in Table 2 to obtain a hot-rolled steel sheet. The rolling end temperature in the hot rolling and the thickness (final thickness) of the obtained hot-rolled steel sheet are also shown in Table 2. Thereafter, the hot-rolled steel sheet was subjected to accelerated cooling under the conditions shown in Table 2 to obtain a steel sheet. The thickness of the obtained steel sheet is the same as the final thickness described above.

[0090] The microstructure, mechanical properties, weather resistance, and fatigue crack propagation properties of each of the obtained steel sheets were evaluated. The evaluation methods are explained below. The results of each evaluation are shown in Table 3.

[0091] (Microstructure) First, a sample for microstructure observation was taken from the 1 / 4t position in the thickness direction of the steel plate so that the longitudinal cross section was the observation surface. Here, the longitudinal cross section refers to a cross section perpendicular to the width direction of the steel plate. Next, the surface of the sample was etched with nital, and the structure was photographed one by one using an optical microscope at 400x and a scanning electron microscope (SEM) at 2000x. The photographed images were used to identify the existing structure. Furthermore, the optical microscope images were analyzed using image analysis software (Photoshop) to divide the bainite region, ferrite region, pearlite region, and martensite region, and the area fraction of each was calculated. Furthermore, the hardness of the martensite identified above was measured based on ISO 14577, and the ratio of martensite with a hardness of 300 HV or more to the total martensite was determined. In the invention examples (steel sheets No. 6 and 27) in which martensite was formed as other structures, the ratio of martensite with a hardness of 300 HV or more to the total martensite was less than 10%.

[0092] (average grain size of bainite) Furthermore, the average grain size of bainite was measured using the above-mentioned microstructure observation sample. In the measurement, first, the surface of the sample was mirror-polished, and the crystal orientation was measured from an electron backscatter diffraction image using an Electron Back-Scattering Pattern (EBSP) device attached to the SEM. Measurements were performed at 0.3 μm intervals within an area surrounded by 200 μm squares, and the area surrounded by grain boundaries with a crystal orientation difference of 15° or more with adjacent crystal grains was defined as a crystal grain, and the average circle equivalent diameter of the crystal grains was obtained. The obtained average circle equivalent diameter was regarded as the average grain size of bainite.

[0093] (mechanical properties) A full thickness tensile test specimen was taken from the width direction (C direction) of the steel plate. Using the full thickness tensile test specimen, a tensile test was carried out in accordance with JIS Z 2241 to measure the yield strength (YS), tensile strength (TS), and total elongation (EL). In the measurement, the type of test specimen to be used was selected in accordance with the provisions of JIS Z 2241. Specifically, a tensile test was first carried out using a JIS 1A test specimen, and as a result, for Examples Nos. 13, 14, 16, 18, and 27 whose tensile strength was 650 MPa or more, a tensile test was carried out again using a JIS 5 test specimen, and the results of the tensile test using the JIS 5 test specimen were adopted.

[0094] In addition, a Charpy impact test specimen was taken parallel to the rolling direction (L direction) from the center of the plate thickness of the steel plate, and a Charpy impact test was carried out at 0° C. in accordance with JIS Z 2202 to measure absorbed energy vE0.

[0095] (weather resistance) A test piece measuring 50 mm × 50 mm × 4 mm was taken from each of the obtained steel plates, and the end faces and back faces of the test piece were sealed with tape, and the front face was also sealed with tape so that the area of ​​the exposed surface was 40 mm × 40 mm. The weather resistance of the test pieces obtained in this manner was evaluated. To evaluate weather resistance, we conducted a corrosion test that simulated the environment inside a girder that is not exposed to rain, which is considered to be the most severe environment for an actual bridge or other structure. The corrosion test was performed by repeating temperature and humidity cycles with salt attached to the sample surface. The temperature and humidity cycle consisted of a drying process at a temperature of 40°C and a relative humidity of 40% RH for 11 hours, followed by a transition period of 1 hour, followed by a wetting process at a temperature of 25°C and a relative humidity of 95% RH for 11 hours, followed by a transition period of 1 hour, for a total of 24 hours per cycle, simulating a temperature and humidity cycle in a real environment. Before the start of the temperature and humidity cycle and every seven cycles, the salt content on the test specimen surface was 1.4 mg / dm 2 Before the drying process, artificial seawater was dropped onto the surface of the test piece so that the Under these conditions, a test was conducted over 26 weeks, covering 182 temperature and humidity cycles. After the corrosion test, the test pieces were immersed in a rust removing solution made of 500 mL of 37% hydrochloric acid, 3.5 g of hexamethylenetetramine, 3 mL of Hibilon (an inhibitor manufactured by Aiko Chemical Co., Ltd.), and distilled water to make 1 L (liter) to remove rust. The weight was measured according to the method described in the 145th Corrosion and Anticorrosion Symposium material "Improvement of the Accuracy of Corrosion Loss Evaluation Methods." Furthermore, the difference between the obtained weight and the initial weight was calculated, and the result was divided by the area of ​​the test surface of the test piece to calculate the average thickness reduction on one side of the test piece. The average thickness reduction was used as an index of weather resistance. An airborne salt level of approximately 0.5 mdd corresponds to an environment with high levels of airborne salt, such as near the coast, but previous knowledge has shown that the amount of steel plate thickness reduction in this corrosion test (over 182 days) is equivalent to the amount of steel plate thickness reduction due to corrosion when exposed to an actual environment with an airborne salt level of approximately 0.5 mdd for 182 days. In addition, when the amount of corrosion after 100 years is calculated by extrapolating the average reduction in plate thickness obtained from the test, if the average reduction in plate thickness obtained during the corrosion test period is 22 μm or less, the average reduction in plate thickness after 100 years is expected to be 0.5 mm or less, at which point no delamination rust will occur. Generally, it is known that the guideline for the suitability of unpainted weathering steel for bridges is a plate thickness reduction of 0.5 mm or less after 100 years, so this corrosion test is carried out on various steel materials, and if the average plate thickness reduction obtained is 22 μm or less, the unpainted weathering steel can be used for bridges. Therefore, in Table 3, weather resistance is judged to be excellent when the average plate thickness reduction is 22 μm or less.

[0096] (Fatigue crack propagation resistance) As an index of fatigue crack propagation resistance, the fatigue crack propagation rate (da / dN) in the plate thickness direction (Z direction), rolling direction (L direction), and width direction (direction perpendicular to the rolling direction, C direction) was calculated using the stress intensity factor range ΔK: 15 MPa / m 1 / 2 and 25MPa / m 1 / 2 The measurements were performed under two conditions. Rolling direction and width direction The fatigue crack propagation rate in the rolling direction (L direction) was measured using a test piece taken from the steel plate so that the load application direction was the rolling direction. Similarly, the fatigue crack propagation rate in the width direction (C direction) was measured using a test piece taken from the steel plate so that the load application direction was the width direction. The test piece was a compact tension test piece in accordance with ASTM E647. In the above-mentioned measurement, a fatigue crack propagation test was performed based on the crack gauge method to determine the fatigue crack propagation rate. Thickness direction On the other hand, to measure the fatigue crack propagation rate in the plate thickness direction (Z direction), a single-side notched simple tension fatigue test piece was used. The above-mentioned test piece was taken from the steel plate, and the fatigue crack propagation rate when the crack propagated in the plate thickness direction was measured.

[0097] As can be seen from the results shown in Table 3, the steel sheets satisfying the conditions of the present invention had extremely excellent properties, satisfying all of the following conditions. In particular, they had both excellent fatigue crack propagation resistance and total elongation, and furthermore, they had excellent fatigue crack propagation resistance in all of the plate thickness direction, rolling direction, and width direction. In contrast, the steel sheets of the comparative examples that did not satisfy the conditions of the present invention did not satisfy at least one of the following conditions. TS:500MPa or more EL: 15% or more (when using JIS No. 1A test piece), EL: 19% or more (when using JIS No. 5 test piece), vE0: 100J or higher Fatigue crack propagation rate in L and C directions: ΔK: 15MPa / m 1 / 2 Under the condition of 1.75×10 -8 (m / cycle) or less, ΔK: 25MPa / m 1 / 2 Under the condition of 8.50×10 -8 (m / cycle) or less, Fatigue crack propagation rate in the Z direction: ΔK: 15MPa / m 1 / 2 Under the condition of 8.75×10 -9 (m / cycle) or less, ΔK: 25MPa / m1 / 2 Under the condition of 4.25×10 -8 (m / cycle) or less, Average plate thickness reduction: 22μm or less

[0098] [Table 1]

[0099] [Table 2]

[0100] [Table 3]

Claims

1. In mass percent, C: 0.010% or more, 0.200% or less, Si: 0.05% or more, 1.00% or less, Mn: 0.20% or more, 2.00% or less, P: 0.001% or more, 0.030% or less, S: 0.0001% or more, 0.0350% or less, Al: 0.001% or more, 0.100% or less, Cu: 0.10% or more, 1.50% or less, Ni: 0.10% or more and 6.00% or less; The balance is Fe and unavoidable impurities, The microstructure of the steel plate contains bainite at an area fraction of 80% or more, The steel plate is characterized in that the average crystal grain size of the bainite is 50 μm or less in terms of circle equivalent diameter.

2. The composition includes, in mass%, Ni: more than 2.00% and not more than 6.00%; Further, in mass percent, Cr: 3.00% or less, Mo: 1.00% or less, W: 1.00% or less, Co: 1.000% or less, Sn: 0.300% or less, Sb: 0.300% or less, Nb: 0.100% or less, V: 0.150% or less, Ti: 0.100% or less, B: 0.0050% or less, Zr: 0.100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, 2. The steel plate according to claim 1, further comprising one or more selected from the following: REM: 0.0200% or less.

3. The method for producing a steel sheet according to claim 1 or 2, A slab having the above-mentioned composition is heated to a temperature range of 1050°C or more and 1250°C or less, After the heating, the slab is heated at a temperature lower than the slab heating temperature, 3 A method for producing a steel sheet, comprising the steps of: hot rolling in a temperature range above a rolling point at which a cumulative rolling reduction is 80% or more.

4. The method for producing a steel sheet according to claim 1 or 2, A slab having the above-mentioned composition is heated to a temperature range of 1050°C or more and 1250°C or less, After the heating, the cumulative rolling reduction in a temperature range of 950° C. or higher is 30% or more; Less than 950°C, Ar 3 A method for manufacturing a steel sheet, comprising the steps of: hot rolling in a temperature range above the rolling point at which a cumulative rolling reduction is 30% or more.

5. After the hot rolling, accelerated cooling is performed, In the accelerated cooling, the cooling start temperature is Ar 3 4. The method for producing a steel sheet according to claim 3, wherein the cooling stop temperature is 700° C. or less and 400° C. or more, and the average cooling rate on the steel sheet surface from the start of cooling to the end of cooling is 2.0° C. / s or more.

6. After the hot rolling, accelerated cooling is performed, In the accelerated cooling, the cooling start temperature is Ar 3 5. The method for producing a steel sheet according to claim 4, wherein the cooling stop temperature is 700° C. or lower and 400° C. or higher, and the average cooling rate on the steel sheet surface from the start of cooling to the end of cooling is 2.0° C. / s or higher.

Citation Information

Patent Citations

  • Production of steel plate having excellent hydrogen induced cracking resistance

    JP1988038519A

  • Production of steel plate having excellent hydrogen induced cracking resistance

    JP1988038520A

  • Steel excellent in fatigue crack propagating property in wet hydrogen sulfide environment

    JP1994322477A

  • Steel plate having fatigue crack arresting effect

    JP1995242992A

  • Ferrite-bainite two-phase steel

    JP1996225882A